Review of the importance of technological pedagogical content knowledge in teaching reading skills - Sarjoni, Musrifah; Abd Rahman, Fadzilah; Sabil, Azhar Md.; Md. Khambari, Masnida (Horizon Research Publishingsubscribe@hrpub.org, 2020)
Malay Language subject is a medium of instruction at primary, secondary and tertiary levels in Malaysia education system. In learning and teaching Malay Language as a formal language, students need to master the four skills of listening, speaking, reading and writing since elementary school. Though reading is an important skill that is able to improve learning motivation as well as language competency, the teaching approach for this skill is always far behind interactive and effective move. In order to facilitate the reading skills according to the need and interests of the present generation, the Malay Language teacher need to master (TPCK). To create an effective learning environment which is more fun and engaging or to enhance the creativity, innovation and stimulation of students related to reading skills is essential and necessary for teachers to master the Technology Pedagogical Content Knowledge (TPCK) in order to create an effective learning environment which is more fun and engaging to enhance the creativity, innovation and stimulation of students. Therefore, review of information and disclosure of experiences related to TPCK in reading skills is essential and necessary as a reference material for the relevant parties.